New Records of Fish Parasitic Isopods (Crustacea: Isopoda) from the Gulf of Thailand - Purivirojkul, Watchariya (Animals (Basel), 2020)
SIMPLE SUMMARY: Parasitic isopods were reported found from marine fishes from many habitat in the world. In Thailand, there is not much study on this parasitic group. This work has compiled all published parasitic isopods documents in Thailand from year 1950 to present include collecting samples from the Gulf of Thailand during the period 2006–2019. New host records were found from four species of parasitic isopods (Cymothoa eremita, Smenispa irregularis, Nerocila sundaica, Norileca triangulata) and two species of parasitic isopods (Argathona macronema, Norileca triangulata) were found first time in the central Indo-Pacific region. ABSTRACT: From a total of 4140 marine fishes examined, eight species of parasitic isopods were reported from marine fishes in the Gulf of Thailand. These isopods were identified in two families, Corallanidae (Argathona macronema and Argathona rhinoceros) and Cymothoidae (Cymothoa eremita, Cymothoa elegans, Smenispa irregularis, Nerocila sundaica, Norileca indica and Norileca triangulata). Most of these parasitic isopods were found in the buccal cavity of their fish hosts with one host recorded as follows: C. eremita was found from Nemipterus hexodon, C. elegans was found from Scatophagus argus, N. sundaica was found from Saurida tumbil. The majority of the isopod specimens recorded in this study was S. irregularis, which was found in the buccal cavities of five host fish, Pampus argentius, Alepes melanoptera, Caranx hippos, Parastromateus niger and Terapon jarbua, with a prevalence of 11.67%, 10.43%, 9.78%, 6.10% and 4.21%, respectively. Argathona rhinoceros was found in the nasal cavity and branchial cavity of Epinephelus coioides, whereas A. macronema and N. triangulata were found on the skin of Epinephelus coioides and Seriolina nigrofasciata, respectively. The highest species diversity was found in E. coioides, which harbored two species of parasitic isopods, A. macronema and A. rhinoceros. Cymothoa eremita, C. elegans, S. irregularis and N. triangulata were recorded for the first time in the Gulf of Thailand. The reported discovery of C. eremita, S. irregularis, N. sundaica and N. triangulata in their fish hosts were new recorded hosts. Moreover, A. macronema and N. triangulata were found for the first time in the central Indo-Pacific region.